THE DELONE MCLEAN MODEL IN EVALUATING THE SUCCESS OF THE SAKTI SYSTEM AT THE CENTRAL JAVA DISTRICT ATTORNEY'S OFFICE - Fariz Saputra, Adi; Nurlaela Wati, Lela; Wibowo, Martino (Penerbit Lafadz Jaya, 2026)
The advancement of information and communication technology (ICT) has driven digital transformation in Indonesia's public finance sector, exemplified by the Agency Level Financial Application System (SAKTI). This study evaluates the success of SAKTI implementation within the District Prosecutor's Offices in the Central Java High Prosecutor's Office jurisdiction by examining the effects of system, information, and service quality on user use and satisfaction, as well as their impact on the organization's net benefits. Using a quantitative approach, data from 270 active users were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results indicate that system quality, information quality, and service quality all have a significant positive effect on both the use of the application and user satisfaction. Furthermore, application use was found to mediate the relationship between these three quality factors and satisfaction. Finally, both application use and user satisfaction were shown to have a significant positive influence on the net benefits perceived by the work units. This study confirms that a holistic approach focusing on system, information, and service quality is crucial for driving user adoption, satisfaction, and ultimately, the successful implementation of e-government financial systems like SAKTI.